Sustained censorship in DZ (2026-03) (Algeria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Algeria. Data sourced from OONI.
Censorship Incident ID: DZ-2026-0111. Severity: critical. Confidence: 77%